The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/toxsci/kfj012
|View full text |Cite
|
Sign up to set email alerts
|

The Endocrine Disruptor Atrazine Accounts for a Dimorphic Somatostatinergic Neuronal Expression Pattern in Mice

Abstract: It has now been established that a large number of man-made and natural chemicals are capable of interfering with the action of natural hormones. In this category "endocrine disruptors" such as the herbicide atrazine, when administered at ecological low doses (1 or 100 microg/kg per day) from gestational day 14 to postnatal day 21, provided a clear dimorphic neurodegenerative pattern in some brain areas of the domestic mouse (Mus musculus). Indeed, the high concentration (100 microg/kg per day) with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…Indeed, Belloni et al indicated that gestational and postnatal exposure to ATR altered motor activity in juvenile offspring and led to extensive neurodegenerative alterations in the cortex, striatum, hippocampus, and hypothalamus in adulthood [13,16]. This suggests that the developing nervous system may be sensitive to ATR, particularly in the early neural developmental stage.…”
Section: Atrazinementioning
confidence: 99%
“…Indeed, Belloni et al indicated that gestational and postnatal exposure to ATR altered motor activity in juvenile offspring and led to extensive neurodegenerative alterations in the cortex, striatum, hippocampus, and hypothalamus in adulthood [13,16]. This suggests that the developing nervous system may be sensitive to ATR, particularly in the early neural developmental stage.…”
Section: Atrazinementioning
confidence: 99%
“…Although data on health effects of ATR in humans are not complete, an increasing number of animal studies report that ATR exposure causes reproductive, developmental, and immunological alterations in laboratory rodents (Cooper et al, 1996Narotsky et al, 2001;Pruett et al, 2003;Filipov et al, 2005;Giusi et al, 2006;Rowe et al, 2006). The brain is another potential target organ for ATR as several in vitro and in vivo studies have suggested that excessive exposure to ATR may be neurotoxic (Das et al, 2000(Das et al, , 2001Rodriguez et al, 2005;Giusi et al, 2006;Coban and Filipov, 2007).…”
mentioning
confidence: 99%
“…The brain is another potential target organ for ATR as several in vitro and in vivo studies have suggested that excessive exposure to ATR may be neurotoxic (Das et al, 2000(Das et al, , 2001Rodriguez et al, 2005;Giusi et al, 2006;Coban and Filipov, 2007). Most of the above-mentioned studies have been performed in rats (Cooper et al, 1996Narotsky et al, 2001;Rodriguez et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Atrazine treatment reduced numbers of tyrosine hydroxylase immunoreactive neurons in the substantia nigra pars compacta and the ventral tegmental area (Coban & Filipov, 2007;Rodriguez et al, 2005), indicating that it is neurotoxic to dopaminergic neurons. Atrazine also caused general neurodegeneration in the hippocampus of the female mouse (Giusi et al, 2006). In vivo microdialysis experiments further showed that dopamine release in the striatum is reduced as a consequence of an acute exposure to atrazine (Rodríguez et al, 2005).…”
Section: Toxic Effects and Mechanism Of Actionmentioning
confidence: 93%